PENGARUH METODE PEMBELAJARAN GAME BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA TOPIK OPERASI HITUNG PERKALIAN MURID KELAS III SDN 3 TONJA KOTA DENPASAR - Anggreni, Kadek; Srie Kusuma Wardhani, Ni Ketut; Ayu Dewi Setiawati, Gusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning is an essential component in developing elementary school students' numeracy skills. However, the results of the Trends in International Mathematics and Science Study (TIMSS) indicate that Indonesian students' mathematics achievement remains relatively low. A similar condition was identified at SD Negeri 3 Tonja, where students' learning outcomes in multiplication operations were low and their participation in learning activities was not optimal. This study aimed to determine whether the Game Based Learning (GBL) method has a significant effect on the mathematics learning outcomes of third-grade students at SD Negeri 3 Tonja, Denpasar. The study employed a quantitative approach using a One Group Pretest–Posttest design involving 28 students. The findings showed that the mean pretest score increased from 66.8 before the implementation of GBL to 78.8 in the posttest after the treatment. The normality test indicated that the pretest data had a significance value of 0.138 (>0.05) and the posttest data had a significance value of 0.147 (>0.05), indicating that both datasets were normally distributed. The paired-samples t-test yielded a calculated t-value of 10.336, which exceeded the critical t-value of 2.052 (df = 27). Therefore, the null hypothesis was rejected, indicating that the GBL method had a significant positive effect on students' mathematics learning outcomes, particularly in multiplication operations.